Critical assessment of environmental sustainability reporting using the GRI G4 guidelines: A case study of the South African gold sector - Viljoen, David Gabriel (Department of Chemical Engineering, 2020)
Sustainability reports ought to be key channels for communication with stakeholders, enhancing organisational accountability and transparency. However, the proliferation of sustainability metrics and the voluntary nature of reporting leads to inconsistencies in the quality of sustainability reporting, invariably affecting its functionality and effectiveness. This research project investigates the quality and functionality of sustainability reporting within the South African gold mining sector. Firstly, a framework for characterising and subsequently assessing the quality of sustainability reports was developed based on a review and analysis of the published literature. This framework was then applied in a multi-method approach consisting of a desktop review involving a content analysis of three company reports that disclose performance according to the GRI G4 Guidelines, and semi-structured interviews with key internal and external stakeholders. The analysis shows that while sustainability reports in the South African mining sector have been found to have beneficial functions for both internal and external stakeholders, they also presented quality issues that are both technical and socio-political in nature. More specifically, the study found that sustainability reports are used internally at an executive level and that the reporting process enhances organisational transparency and accountability. Externally, sustainability reports were found to be used as a source of performance information and as an indicator of company commitment and legitimacy. However, the quality issues, namely levels of aggregation and detail, as well as the degree of integrity, were considered to have a negative effect on the functionality and effectiveness of sustainability reports for stakeholders. This study offers insight into how companies report and how stakeholders perceive and relate to sustainability reporting, and in turn serves to highlight both strengths that should be encouraged, and weaknesses that detract from sustainability reports’ effectiveness and functionality. The application of a multi-criteria framework in a multi-method approach provides a more holistic picture of the quality and functionality of sustainability reports, allowing technical and political quality issues to be discussed in a simultaneous study, as well as highlighting the complexities and nuances of sustainability reporting.